On resonance and frequency response characteristics of electrical circuits - Drieberg, M. (Manchester University Press, 2013)
While teaching network analysis to undergraduate students, the frequency response of electrical circuits consisting of passive elements such as resistors, capacitors and inductors are commonly analysed. Students are familiar with the sharp amplitude peak or trough normally occurring at resonance. This observation is not only intuitively pleasing, but also consistent with the concept of resonance in many physical systems. In the well-known series and parallel RLC circuits, the maximum and minimum currents, respectively, occur at resonance. Because of this, many students and even instructors (sometimes) may erroneously assume that the resonance in general RLC circuits implies maximum or minimum current. In this paper, it will be shown that this is generally untrue. The theoretical analyses and experimental validation of series, parallel and series-parallel RLC circuits are presented to address this common misconception. Â© Manchester University Press.